Improved regeneration of eggplant doubled haploids from microspore-derived calli through organogenesis - Rivas Sendra, Alba (2017)
Doubled haploid (DH) technology allows for the production of pure lines, useful for plant breeding, through a one-generation procedure that reduces considerably the time and resources needed to produce them. Despite the advantages of microspore culture to obtain DHs, this technique is still insufficiently developed in eggplant, where DHs are produced from microspore-derived calli through organogenesis. At present, very little is known on the best in vitro conditions to promote this process. This is why in this work we addressed the optimization of the process of regeneration of eggplant DH plants from microspore-derived calli. We evaluated the effect of different media compositions in the induction of organogenesis, in the promotion of shoot growth and elongation, and in root growth. According to our results, we propose the repeated subculture of the calli in MS medium with 0.2 mg/l IAA and 4 mg/l zeatin to produce shoots, and then the repeated subculture of the excised shoots in basal MS medium to promote their conversion into entire plantlets. This procedure yielded 7.6 plants per 100 cultured calli, which represents a ~4× increase with respect to previous reports. We also evaluated by flow cytometry and SSR molecular markers the effect of these in vitro culture conditions in the rate of DH plant production, finding that ~70 % of the regenerated plants were true DHs. These results substantially improve the efficiencies of DH recovery published to date in eggplant, and may be useful to those working in the field of eggplant doubled haploidy and breeding.